2016
DOI: 10.1039/c5sc03591k
|View full text |Cite
|
Sign up to set email alerts
|

Single near-infrared fluorescent probe with high- and low-sensitivity sites for sensing different concentration ranges of biological thiols with distinct modes of fluorescence signals

Abstract: We describe a unique approach for the development of an interesting type of the fluorescent probes, which can show different modes of fluorescence signals to distinct concentration ranges of a target of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…A PO-120 quartz cuvette (10 mm) was purchased from Shanghai Huamei Experiment Instrument Plants, China. 1 H NMR, 13 C NMR spectra were recorded on a BRUKER AVANCE III HD spectrometer. ESI determinations were carried out on AB Triple TOF 5600 plus System (AB SCIEX, Framingham, USA).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A PO-120 quartz cuvette (10 mm) was purchased from Shanghai Huamei Experiment Instrument Plants, China. 1 H NMR, 13 C NMR spectra were recorded on a BRUKER AVANCE III HD spectrometer. ESI determinations were carried out on AB Triple TOF 5600 plus System (AB SCIEX, Framingham, USA).…”
Section: Instrumentsmentioning
confidence: 99%
“…In recent times, fluorescent molecular probes have emerged as an attractive tool for selective detection of various chemical and biological components [6][7][8][9][10], including thiols [11][12][13][14][15][16][17]. Compared to traditional techniques, chemical probes based on absorption or fluorescence changes are more feasible for detecting analyses owing to their many appealing advantages such as low detection limit, high selectivity, its real-time monitoring and its potential for vivo imaging of living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, uorescence analysis system has been widely used to detect metal ions, anions and biomolecules due to its simplicity, high sensitivity, and instantaneous response. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, available uorescent probes for hydrazine are still very limited and most of them are turn-on types.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [127] reported the new NIR fluorescent probe chloro-hydroxyl-merocyanine-thiol or (CHMC-thiol) containing 2,4-dinitrobenzenesulfonate moiety as a fluorescence quencher. The nucleophilic substitution by thiols of the chloro moiety in the chloro-substituted cyanine conjugate can induce a ratiometric mode in fluorescence of the probe CHMC-thiol.…”
Section: Fluorescent Dyes As "Molecular Photoswiches" and Molecular Cmentioning
confidence: 99%